2009
DOI: 10.3748/wjg.15.1493
|View full text |Cite
|
Sign up to set email alerts
|

Hirschsprung’s disease: Is there a relationship between mast cells and nerve fibers?

Abstract: AIM:To define the topography of mast cells and their numbers in cases of Hirschsprung's disease (HD) and non-HD, assess neural hypertrophy using imaging software and to study the relationship between mast cells and nerve fibers. METHODS:HE stained sections of 32 cases of chronic constipation in the age group of 0-14 years were reviewed for ganglion cells. AChE staining was performed on frozen sections of colonic and rectal biopsies. Based on their findings cases were divided into HD and non-HD and mast cells s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…However, MC have been less extensively studied in patients complaining of constipation. Apart from sporadic observations of an increased number of colonic mucosal MC in constipation‐predominant IBS patients, 38 the only available studies in constipated patients were obtained in chagasic patients 10–12 and in those with Hirschsprung’s disease 13–16 . Concerning Chagas’ disease, the increase of MC found in these subjects has been put in relation to the increased fibrosis found in the colon of these patients, 11 whereas in Hirschsprung’s disease this increase has been hypothesised as a possible mechanism of ENS reparation 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, MC have been less extensively studied in patients complaining of constipation. Apart from sporadic observations of an increased number of colonic mucosal MC in constipation‐predominant IBS patients, 38 the only available studies in constipated patients were obtained in chagasic patients 10–12 and in those with Hirschsprung’s disease 13–16 . Concerning Chagas’ disease, the increase of MC found in these subjects has been put in relation to the increased fibrosis found in the colon of these patients, 11 whereas in Hirschsprung’s disease this increase has been hypothesised as a possible mechanism of ENS reparation 15 …”
Section: Discussionmentioning
confidence: 99%
“…However, MC could also play some role in other pathological conditions characterised by constipation as expression of an abnormal motility of the colon. For instance, it has been shown that patients with megacolon because of Chagas’s disease display an increased number of MC in the colon 10–12 and the same is true for patients with Hirschsprung’s disease 13–16 …”
Section: Introductionmentioning
confidence: 96%
“…Yadav et al [19] report assessment of neural hypertrophy using Scion image analysis software. Images of relevant areas were analyzed and the size and perimeter of the thickest nerve fiber in the submucosa were measured, the number of nerve fibers was counted.…”
Section: Manual Evaluationmentioning
confidence: 99%
“…Despite extensive research, the pathogenesis of the disease is not fully understood. There have been reports suggesting that MCs may play a role in the development of HD [58,60-62].…”
Section: Hirschsprung’s Disease (Hd) and Intestinal Neuronal Dysplasimentioning
confidence: 99%